Correlation of Platelet Indices with Severity of Gastroesophageal Varices in Patients of Liver Cirrhosis: A Research Protocol - Parav Tantia; Sourya Acharya (Journal of Clinical and Diagnostic Research)
Introduction: In India, liver cirrhosis is a significant public health concern, contributing to 2.95% of total deaths. Cirrhosis is the advanced stage of ongoing liver fibrosis, which poses substantial global health challenges due to its fatal consequences, such as gastroesophageal varices. Need of the study: Gastroesophageal varices are a potentially lethal complication of liver cirrhosis. The severity of these varices directly impacts the prognosis of the patient. Gastroesophageal varices are major contributors to both mortality and morbidity on a global scale. While various parameters have been explored to predict the progression and severity of these varices, platelet indices have not been extensively studied in cirrhosis patients with gastroesophageal varices in India. Aim: To study the association and correlation of platelet indices with the severity of gastroesophageal varices in patients with liver cirrhosis. Materials and Methods: A cross-sectional study will be conducted in the Medicine OPD/IPD of Acharya Vinoba Bhave Rural Hospital (AVBRH), Wardha, Maharashtra, India from May 2023 to May 2025, involving 64 patients who meet the inclusion and exclusion criteria. Patients fulfilling the selection criteria will be informed about the study procedure in their native language. The diagnosis of liver cirrhosis will be established based on the patient’s detailed history, physical examination, laboratory tests, and ultrasound scan. Upon enrollment, a detailed history will be taken, and parameters will be recorded in a specifically designed proforma. Initial parameters will include age, gender, weight, co-morbidities (such as Diabetes Mellitus (DM), Hypertension (HTN), Heart Failure (HF), Cardiovascular Disease (CVS), Chronic Obstructive Pulmonary Disease (COPD), kidney failure, liver failure, and malignant conditions), and the aetiology of cirrhosis. Platelet count and indices-Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), and Plateletcrit (PCT)-will be assessed. The categorical and continuous variables will be represented as frequency (percentage) and mean (standard deviation, SD). The Chi-square test and Independent sample t-test will be used to evaluate the association between various categorical variables and continuous variables. The Pearson correlation test will be used to assess any correlation between platelet indices and oesophageal varices, with a significance level set at <0.05.